Koordinasi Rele Pada Jaringan Transmisi 150 kV - Anharul Azmi; Eddy Hamdani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Power transmission system is of one component in the supply of electricity. Then it takes one of transmission system good. To maintain of transmission system good needed protection system accordance with the requirements of protection . protection system functioning of to localize disturbance as small as possible . protection system of transmission normally using of distance relay and OCR-GFR relay. distance relay serves as a main security and OCR-GFR for as backup. calculation of short circuit and relay coordination using digsilent program 14.1.3. based on the results of calculations and simulations showed that the distance relay coordination is good and necessary for resetting the relay OCR-GFR due to changes in short circuit.Keywords: transmission, coordination, distance relay, ocr-gfr relay, ETAP